Κατευθυντήριες γραμμές για την ορθή γεωργική πρακτική και συγκομιδή φαρμακευτικών και αρωματικών φυτών - Μαυροθέρης, Λευτέρης (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Unquestionably, great importance is attributed to the Medicinal and Aromatic Plants, both for their fragrance and their healing properties, derived either from a dry drug or their essential oils. Essential oils are widely used in perfumery, soap, confectionary, toothpastes, food industry, pharmaceuticals etc. Dry drugs can be used both for making beverages/brews and for certain medicinal substances, such as alkaloids, flavonoids, glycosides etc. Aromatic and medicinal plants were, since ancient times and are to date, of very high economic importance. Guidelines on Good Agricultural Practice and Harvesting of Medicinal and Aromatic Plants (Guidelines for Good Agricultural and Wild Collection Practices of Medicinal and Aromatic Plants, GACP‐MAP) , of which a detailed report will be made in this paper, were compiled and published by EUROPAM (European Herb Growers Association). The aforementioned guidelines were written in the English language, which negatively affects their understanding and comprehension, by a large number of Greek-speaking agricultural producers. The purpose of this paper is to render these guidelines in the Greek language. Guidelines on Good Agricultural Practice and Harvesting of Medicinal and Aromatic Plants, are intended to apply to cultivation, wild collection and practices of primary processing of all plants and their derivatives, which are marketed or used in the European Union. Therefore, they apply to the production of all plant materials used either directly or processed and prepared for humans and/or animals. Moreover, they apply to all ways of production, including organic production, in accordance with EU regulations. Additionally, this paper will give a brief history of the subject and cite related definitions and offer information with regards to essential oils and their collection. This paper will also make reference to the use of Essential and Medicinal Plants, as well as to their economic importance, as related to the general economic crisis in Cyprus. Finally, reference will be made to the main, from a commercial point of view, aromatic and medicinal plants of Cyprus, as well as related information and visual images.
Keywords: Medicinal and Aromatic Plants; Guidelines for Good Agricultural and Wild Collection Practices; (GACP‐MAP); MAP; Αρωματικά και Φαρμακευτικά Φυτά; Κατευθυντήριες Γραμμές Ορθής Γεωργικής Πρακτικής και Συγκομιδής; Α.Φ.Φ